2008
DOI: 10.1016/j.jcat.2008.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Stability of bimetallic Pd–Zn catalysts for the steam reforming of methanol

Abstract: ZnO-supported palladium-based catalysts have been shown in recent years to be both active and selective towards the steam reforming of methanol, although they are still considered to be less active than traditional copper-based catalysts. The activity of PdZn catalysts can be significantly improved by supporting them on alumina. Here we show that the Pd/ZnO/Al 2 O 3 catalysts have better long-term stability when compared with commercial Cu/ZnO/Al 2 O 3 catalysts, and that they are also stable under redox cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
129
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(145 citation statements)
references
References 27 publications
13
129
1
2
Order By: Relevance
“…10). This vibrational frequency agrees well with the on-top CO peak reported for PdZn-ZnO-Al 2 O 3 powder catalysts, after hydrogen reduction/activation of the catalyst [37]. After annealing in 10 -6 mbar CO to 473 K, which in the range of the alloy stability window, the PdZn alloy was clearly established.…”
Section: Pdzn Multilayer Surface Alloy: Thermochemical Stability Undesupporting
confidence: 88%
See 2 more Smart Citations
“…10). This vibrational frequency agrees well with the on-top CO peak reported for PdZn-ZnO-Al 2 O 3 powder catalysts, after hydrogen reduction/activation of the catalyst [37]. After annealing in 10 -6 mbar CO to 473 K, which in the range of the alloy stability window, the PdZn alloy was clearly established.…”
Section: Pdzn Multilayer Surface Alloy: Thermochemical Stability Undesupporting
confidence: 88%
“…As some form of surface-bonded formaldehyde may either become quickly oxidized by interaction with the observed Zn-O(H) species or is simply thermally desorbed to the gas phase, the relative probabilities of thermal desorption as competing "chemical reaction" to total oxidation will determine the product partial pressure ratio. If the overall rate-limiting step is located within the dehydrogenation steps prior to formaldehyde, both the subsequent formaldehyde desorption and total oxidation pathways should be much faster, which can explain the observed simultaneous formation of CO 2 and CH 2 O up to 573 K. This scenario is supported by Ranganathan et al [37], who reported a faster conversion of formaldehyde than methanol toward CO 2 under otherwise identical reaction conditions. Moreover, the reaction probability toward CO 2 appears to be much higher on the supported PdZn/ZnO systems, which may be attributed to the much higher abundance of ZnO surface or ZnO/PdZn interface sites, i.e.…”
Section: Msr On Clean Pd Vs "Monolayer" Vs "Multilayer" Pdzn Surfacmentioning
confidence: 82%
See 1 more Smart Citation
“…Low temperature steam reforming mainly focuses on Cu-based [3][4][5][6][7][8][9][10][11][12][13][14][15] and Pd-based [16][17][18][19][20][21][22] catalysts. For Cu-based catalysts, the most extensively studied catalysts are Cu/ZnO and Cu/ZnO/Al 2 O 3 [7,9,10], etc.…”
Section: Introductionmentioning
confidence: 99%
“…CeO 2 can hinder the Cu sintering and enhance the thermal stability of catalysts [14]. Apart from Cu-based catalyst, Pd-based catalyst is another promising low temperature steam reforming catalyst [16][17][18][19][20][21][22]. Iwasa et al [20] first found Pd/ZnO had good activity, CO 2 selectivity and thermal stability for low temperature steam reforming of methanol, and all these were attributed to the formation of PdZn alloy.…”
Section: Introductionmentioning
confidence: 99%